(untitled) (REMUNOM, 2025)
Introduction: This study aimed to synthesize pharmaceutical interventions used to improve medication adherence in elderly individuals with chronic diseases. Therefore, it is important to emphasize that with the aging process comes the emergence of chronic diseases, which constitute one of the main aggravating factors for death and functional restrictions worldwide, thus highlighting the need for pharmaceutical intervention to improve treatment adherence in this population. Method: The research was developed through an integrative literature review, with a qualitative and descriptive approach. The scientific productions were analyzed through a systematic search of the Latin American and Caribbean Literature in Health Sciences (LILACS), Electronic Library Online (SciELO), and United States National Library of Medicine (PubMed) databases, using the following keyword combinations: "medication adherence," "chronic diseases," "elderly," and "pharmaceutical care." These terms were combined using the Boolean operator AND to narrow the results. Results: Based on this, it was possible to identify that the role of the pharmacist is essential in improving medication adherence among elderly individuals with chronic diseases. This can occur through dialogue with the individual about their treatment, as well as individual interviews, counseling on the correct use of medications, and the suggestion of using pill boxes marked with the days of the week. Conclusion: It was evident that the role of the pharmacist is essential for improving medication adherence in patients with chronic diseases.